Cloud-Native Security Posture Management in Amazon Web Services (AWS). - Ratemo, Michael (linkedin.com, 2024)
Learn how to implement cloud security posture management in AWS to gain visibility into threats, vulnerabilities, misconfigurations and compliance issues in the cloud.